(untitled) (Research, Society and Development, 2020)
Flour production is a way to use parts of fruits and vegetables that are discarded and an alternative in the production of gluten-free products, together with rice flour. The objective was to evaluate the physical and chemical characteristics of rice flour (RF), pineapple peel flour (PPF), banana peel flour (BPF) and pumpkin seed flour (PSF). RF was acquired in market. The banana and pineapple peels were dried in a tray dehydrator and the pumpkin seeds roasted on an industrial stove, then ground and analyzed. The BPF showed a lower L* value, that is, darker, in addition to a lower hue angle and a higher a* value, the opposite result was observed in RF. BPF had a higher moisture content (9.91%), followed by RF (7.95%), PPF (5.67%) and PSF (4.11%). The PSF had a high content of lipids (35.41%). PPF and BPF had the highest soluble fibers contents (5.25% and 6.20%, respectively) and PPF the highest insoluble fiber content (45.06%). No trypsin inhibiting activity was detected in the flours. PPF and BPF had the highest total phenolics contents, thus greater antioxidant activity. The PSF presented among the set of its phenolics, compounds with greater antioxidant power, due to the higher PAOXI index. It is concluded that the PPF, BPF and PSF presented high fiber content, total phenolics and antioxidant activity, being an option for food enrichment.